Secundum Naturam Vivere : the stoic telos and practical guidance for the attainment of a happy life in Seneca’s epistulae morales - Raal, Eva-Melitta (Stellenbosch : Stellenbosch University, 2011)
Thesis (MA)--Stellenbosch University, 2011.